The Role of Universities in Empowering Individuals and Society in Afghanistan - YAR, Fayaz Gul Mazloum; MUZAMMIL, Hameedullah (Integration: Journal Of Social Sciences And Culture, 2025)
Purpose:The primary objective of this research is to examine the role of universities as the highest educational and training institutions in empowering individuals and society. Initially, the study explored the literal and terminological meanings of empowerment. Then, we highlight the most essential functions of universities concerning individual and societal empowerment.Methodology:After clarifying universities' role as the highest educational and training institutions, we addressed how universities can effectively empower individuals and society. This research adopts an analytical approach that examines and analyzes expert opinions, literature reviews, and previous studies.Findings:As the highest educational and training institutions, universities play a crucial role in expanding the frontiers of knowledge, conducting research, providing public services, and empowering individuals and society in various scientific, cultural, social, and political dimensions. They should critically study and systematically, sequentially, and densely transmit Afghanistan's rich Islamic heritage to students, creating a constructive link between traditional and modern cultures.Implication:Universities are expected to define the significant issues humanity faces and identify the dynamic forces of the present time. Ultimately, by fostering creativity, innovation, and a spirit of research, reasoning, critical thinking, and initiative among students, universities can fulfill their grand role in empowering individuals and society.